New Modified Conformable Fractional Integral Inequalities of Hermite–Hadamard Type with Applications - Thabet Abdeljawad; Pshtiwan Othman Mohammed; Artion Kashuri (Journal of Function Spaces)
In this study, a few inequalities of Hermite–Hadamard type are constructed via the conformable fractional operators so that the normal version is recovered in its limit for the conformable fractional parameter. Finally, we present some examples to demonstrate the usefulness of conformable fractional inequalities in the context of special means of the positive numbers.